Bruch membrane opening detection accuracy in healthy eyes and eyes with glaucoma with and without axial high myopia in an American and Korean cohort - Rezapour, Jasmin; Proudfoot, James A.; Bowd, Christopher; Dohleman, Jade; Christopher, Mark; Belghith, Akram; Vega, Suzanne M.; Dirkes, Keri; Suh, Min Hee; Jonas, Jost B.; Hyman, Leslie; Fazio, Massimo A.; et al. (American journal of ophthalmology, 2022)
Purpose - To determine the predictors of Bruch membrane opening (BMO) location accuracy and the visibility of the BMO location in glaucoma and healthy individuals with and without axial high myopia. - Design - Cross-sectional study. - Methods - Healthy eyes and eyes with glaucoma from an American study and a Korean clinic population were classified into 2 groups: those with no axial high myopia (axial length [AL] <26 mm) and those with axial high myopia (AL ≥26 mm). The accuracy of the automated BMO location on optic nerve head Spectralis optical coherence tomography radial scans was assessed by expert reviewers. - Results - Four hundred thirty-eight non-highly myopic eyes (263 subjects) and 113 highly myopic eyes (81 subjects) were included. In healthy eyes with and without axial high myopia, 9.1% and 1.7% had indiscernible BMOs while 54.5% and 87.6% were accurately segmented, respectively. More than a third (36.4%) and 10.7% of eyes with indiscernible BMOs were manually correctable (respectively, P = .017). In eyes with glaucoma with and without high myopia, 15.0% and 3.2% had indiscernible BMOs, 55.0% and 38.2% were manually corrected, and 30.0% and 58.7% were accurately segmented without the need for manual correction (respectively, P = .005). Having axial high myopia, a larger AL, a larger BMO tilt angle, a lower BMO ovality index (more oval), and a glaucoma diagnosis were significant predictors of BMO location inaccuracy in multivariable logistic regression analysis. - Conclusions - As BMO location inaccuracy was 2.4 times more likely in eyes with high axial myopia regardless of diagnosis, optical coherence tomography images of high myopes should be reviewed carefully, and when possible, BMO location should be corrected before using optic nerve head scan results for the clinical management of glaucoma.
Online veröffentlicht: 10. Dezember 2021, Artikelversion: 28. Januar 2022
Gesehen am 05.03.2024